Anti-virulence effects of aqueous pomegranate peel extract on E. coli urinary tract infection - Zam, Wissam; Khaddour, Aziz (Progress in Nutrition, 2017)
Urinary tract infections (UTIs) are among the most prevailing infectious diseases and may be classified as uncomplicated or complicated, depending upon the urinary tract anatomy and physiology. The Gram negative bacteria of E. coli cause 70-95% of upper and lower UTIs. Pomegranate peels (Punica granatum L.) are considered byproducts obtained during juice processing and characterized by the significant presence of polyphenols associated with biological properties such as antimicrobial and antioxidant agents. The aim of this study was to estimate the antimicrobial and anti-virulence effect of aqueous pomegranate peel extract against E. coli cultures collected from urinary cultures of the Microbiology Laboratory of Al-Bassel Hospital, in Syria, 2016. The inhibitory activity was found to be dose and pH dependent with an MIC value of 0.6 mg/ml and an MBC value of 1.2 mg/ml at the pH of the aqueous extract (3.5). The assay of adhesion carried out at MIC showed a reduction of up to 80% of the adhesion index accompanied with a reduction in motility and ornithine decarboxylation as indicated by MIO test. Results indicate that the aqueous pomegranate peel extract could be an important source of new antimicrobial compounds in order to treat E. coli urinary tract infections.